2005
DOI: 10.1016/j.forsciint.2004.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Inference of human geographic origins using Alu insertion polymorphisms

Abstract: The inference of an individual's geographic ancestry or origin can be critical in narrowing the field of potential suspects in a criminal investigation. Most current technologies rely on single nucleotide polymorphism (SNP) genotypes to accomplish this task. However, SNPs can introduce homoplasy into an analysis since they can be identical-by-state. We introduce the use of insertion polymorphisms based on short interspersed elements (SINEs) as a potential alternative to SNPs. SINE polymorphisms are identical-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
(54 reference statements)
2
43
0
6
Order By: Relevance
“…The remaining 46 CHGS polymorphic elements were likely from the public human BAC sequences that may have not been used for the assembly of PHGS. To determine how many of the 800 polymorphic Alu elements had been previously identified and published, we compiled a database containing 1051 non-redundant polymorphic Alu insertions (http://falcon.roswellpark.org:9090; Wang et al, in press) from the over 1500 polymorphisms reported in the literature (Batzer et al, 1994Bennett et al, 2004;Callinan et al, 2003;Carroll et al, 2001;Carter et al, 2004;Garber et al, 2005;Mamedov et al, 2005;Otieno et al, 2004;Ray et al, 2005;Roy-Engel et al, 2001;Watkins et al, 2003;Xing et al, 2003). A comparison of the genomic locations of our 800 polymorphic Alu insertions with the list revealed that only 266 of the 800 Alu elements correspond with previously reported Alu repeats, suggesting that the remaining 534 insertions represent newly identified polymorphisms.…”
Section: Identification Of Alu Insertion Polymorphismsmentioning
confidence: 99%
“…The remaining 46 CHGS polymorphic elements were likely from the public human BAC sequences that may have not been used for the assembly of PHGS. To determine how many of the 800 polymorphic Alu elements had been previously identified and published, we compiled a database containing 1051 non-redundant polymorphic Alu insertions (http://falcon.roswellpark.org:9090; Wang et al, in press) from the over 1500 polymorphisms reported in the literature (Batzer et al, 1994Bennett et al, 2004;Callinan et al, 2003;Carroll et al, 2001;Carter et al, 2004;Garber et al, 2005;Mamedov et al, 2005;Otieno et al, 2004;Ray et al, 2005;Roy-Engel et al, 2001;Watkins et al, 2003;Xing et al, 2003). A comparison of the genomic locations of our 800 polymorphic Alu insertions with the list revealed that only 266 of the 800 Alu elements correspond with previously reported Alu repeats, suggesting that the remaining 534 insertions represent newly identified polymorphisms.…”
Section: Identification Of Alu Insertion Polymorphismsmentioning
confidence: 99%
“…In the past decade, a new type of MGMs based on RE insertion polymorphism has become popular in population studies. [28][29][30][31][32] These markers belong to a biallelic indel (insertion/deletion) polymorphism type and are characterized by several features making them good candidates for human genetic identification. Multiple studies intended to identify new polymorphic RE insertions resulted in an increasing number of candidate MGMs scattered across the whole human genome.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in collaboration with law enforcement officials, forensic DNA specimens were evaluated using the dataset of 100 Alu insertion polymorphisms and Structure 2.0. The system demonstrated accurate assignment of each specimen to the correct geographic affiliation [109].…”
Section: Alu Insertion Polymorphisms and Inference Of Ancestrymentioning
confidence: 99%